Floating drug delivery systems: A better approach - Abhishek Chandel; Kapil Chauhan; Bharat Parashar; Hitesh Kumar; Sonia Arora (2012)
The purpose of writing this review on floating drug delivery systems (FDDS) was to compile the recent literature with special focus on the principal mechanism of floatation to achieve gastric retention. It is known that differences in gastric physiology (such as, gastric pH, motility) exhibit both intra- as well as inter-subject variability demonstrating significant impact on gastric retention time and drug delivery behaviour. The recent developments of FDDS including the physiological and formulation variables affecting gastric retention, approaches to design single-unit and multiple-unit floating systems, and their classification and formulation aspects are covered in detail. This review also summarizes the studies to evaluate the performance and application of floating systems, and applications of these systems.DOI: http://dx.doi.org/10.3329/icpj.v1i5.10283International Current Pharmaceutical Journal 2012, 1(5): 110-118